2022
DOI: 10.1007/s11418-022-01672-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the antibacterial activities of cannabinoid biosynthetic intermediate, olivetolic acid, and its alkyl-chain derivatives

Abstract: Investigations of antibacterial activities revealed that the incorporation of longer alkyl chains to the C-6 position in resorcylic acid conferred antibacterial properties against Staphylococcus aureus and Bacillus subtilis . The resultant olivetolic acid (OA) derivatives with n -undecyl and n -tridecyl side-chains, even those lacking the hydrophobic geranyl moiety from their C-3 positions, exhibited strong antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Due to its size, an extended or branched alkyl chain attached to the resorcylate core will is likely to fit into the pocket. This has been demonstrated in converting an analog containing a tridecane side chain to CBGA‐C13, but the ratio of possible products formed is unknown [25] . Previous studies have reported that olivetolic acid derivatives with shorter alkyl chains, such as the methyl or propyl chain, are converted to CBGA‐C1 and CBGA‐C3, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its size, an extended or branched alkyl chain attached to the resorcylate core will is likely to fit into the pocket. This has been demonstrated in converting an analog containing a tridecane side chain to CBGA‐C13, but the ratio of possible products formed is unknown [25] . Previous studies have reported that olivetolic acid derivatives with shorter alkyl chains, such as the methyl or propyl chain, are converted to CBGA‐C1 and CBGA‐C3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated in converting an analog containing a tridecane side chain to CBGA-C13, but the ratio of possible products formed is unknown. [25] Previous studies have reported that olivetolic acid derivatives with shorter alkyl chains, such as the methyl or propyl chain, are converted to CBGA-C1 and CBGA-C3, respectively. Orsellinic acid is converted to various products by the NphB wild type.…”
Section: Docking Studies To Predict Nphb Substrate Acceptancementioning
confidence: 99%
“…Furthermore, recent in vitro studies highlight the potential of NphB to produce of both natural and unnatural derivatives of CBGA‐C5. [ 30,31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent in vitro studies highlight the potential of NphB to produce of both natural and unnatural derivatives of CBGA-C5. [30,31] A first in vivo approach of NphB using E. coli as heterologous host organism for the production of CBGA-C5 and CBGA-C3 was reported in 2019. The group produced 1 mg L −1 CBGA-C5 from glycerol and 200 mg L −1 OA, as well as 5 mg L −1 CBGA-C3 from glycerol and 200 mg L −1 divarinic acid.…”
mentioning
confidence: 99%
“…22 It has been found to have antifungal and antibacterial properties, as well as potential anti-inammatory and anti-cancer effects. 23,24 However, despite their promising biological properties, limited studies have been conducted on their antioxidant capacity. This is a signicant limitation, as these compounds have the potential to be used as natural alternatives to toxic synthetic compounds like BHT and BHA, which are commonly used as preservatives in the food industry.…”
Section: Introductionmentioning
confidence: 99%